2022
DOI: 10.3390/ijms232314835
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Potentiality of Flavonoids on Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD), due to its spread, has become a global health priority, and is characterized by senile dementia and progressive disability. The main cause of AD and other neurodegenerations (Huntington, Parkinson, Amyotrophic Lateral Sclerosis) are aggregated protein accumulation and oxidative damage. Recent research on secondary metabolites of plants such as polyphenols demonstrated that they may slow the progression of AD. The flavonoids’ mechanism of action in AD involved the inhibition of acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 219 publications
0
37
0
Order By: Relevance
“…Psychedelics can produce sustained therapeutic benefit following a single administration, and also have broad therapeutic value and efficacy in the treatment of disorders, such as depression, post-traumatic stress, anxiety disorders, and addictive substance and alcohol abuse disorders [ 11 ]. A number of flavonoids have been identified with an ability to regulate neural functional properties of potential therapeutic value in the treatment of neurological disorders [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. One class of flavonoid metabolite (urolithins) shows particular promise in the treatment of neurodegenerative disorders and in the provision of general health and wellbeing [ 20 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychedelics can produce sustained therapeutic benefit following a single administration, and also have broad therapeutic value and efficacy in the treatment of disorders, such as depression, post-traumatic stress, anxiety disorders, and addictive substance and alcohol abuse disorders [ 11 ]. A number of flavonoids have been identified with an ability to regulate neural functional properties of potential therapeutic value in the treatment of neurological disorders [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. One class of flavonoid metabolite (urolithins) shows particular promise in the treatment of neurodegenerative disorders and in the provision of general health and wellbeing [ 20 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dubois et al, 2019 [ 72 ] showed that AKT3 modulates protection against demyelinating inflammatory disorder. Nutraceutical intervention of the PI3K-AKT pathway in microglial regulation may be promising to consider [ 78 ]. EGCG downregulation of AKT3 may utilize an anti-aging function that mediates AKT3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is still a lack of clinical evidence for these promising flavonoids. We discovered a clinical study that began in 2022 and will end in 2024 to determine the efficacy and safety of cotton flavonoid tablets for the treatment of AD (Calderaro et al, 2022).…”
Section: Othersmentioning
confidence: 99%
“…Unfortunately, there is still a lack of clinical evidence for these promising flavonoids. We discovered a clinical study that began in 2022 and will end in 2024 to determine the efficacy and safety of cotton flavonoid tablets for the treatment of AD (Calderaro et al, 2022). Although the exact mechanisms of action are unclear, several important physiological responses regulated by flavonoids may be key to promoting the neuroprotective effect of AD.…”
Section: Anti‐ad Active Ingredients In Plantsmentioning
confidence: 99%